Influence of guanine nucleotides on complex formation between Ras and CDC25 proteins. - Lai, C C (1993)
The Saccharomyces cerevisiae CDC25 gene and closely homologous genes in other eukaryotes encode guanine nucleotide exchange factors for Ras proteins. We have determined the minimal region of the budding yeast CDC25 gene capable of activity in vivo. The region required for full biological activity is approximately 450 residues and contains two segments homologous to other proteins: one found in both Ras-specific exchange factors and the more distant Bud5 and Lte1 proteins, and a smaller segment of 48 amino acids found only in the Ras-specific exchange factors. When expressed in Escherichia coli as a fusion protein, this region of CDC25 was found to be a potent catalyst of GDP-GTP exchange on yeast Ras2 as well as human p21H-ras but inactive in promoting exchange on the Ras-related proteins Ypt1 and Rsr1. The CDC25 fusion protein catalyzed replacement of GDP-bound to Ras2 with GTP (activation) more efficiently than that of the reverse reaction of replacement of GTP for GDP (deactivation), consistent with prior genetic analysis of CDC25 which indicated a positive role in the activation of Ras. To more directly study the physical interaction of CDC25 and Ras proteins, we developed a protein-protein binding assay. We determined that CDC25 binds tightly to Ras2 protein only in the absence of guanine nucleotides. This higher affinity of CDC25 for the nucleotide-free form than for either the GDP- or GTP-bound form suggests that CDC25 catalyzes exchange of guanine nucleotides bound to Ras proteins by stabilization of the transitory nucleotide-free state.